Energetic expenditure of the referee and the assistant soccer referee - Silva, Alberto Inácio da; Rodriguez-Añez, Ciro Romelio (Journal of Physical Education (Maringá), 2008)
The aim of this work was to estimate the energetic expenditure of the soccer referee and the assistant soccer referee during a soccer game. Fourteen soccer referees from Curitiba city were observed, 9 acting as referees (mean age of 36.3 years and body mass of 82 kg) and 5 as assistant referees (mean age of 30 years and body mass of 77 kg). They were filmed during official state and national games. The time spent by the referees in each motor action was chronometered by watching the tapes. The energetic expenditure was estimated determining oxygen consumption through the equation suggested by the ACSM (1980) for running and sprinting and the equation suggested by Bubb, Martin and Howley apud Vivacqua e Hespanha (1992) for walking and jogging. The oxygen consumption is a function that depends on the intensity of the realized work and on the dislocated mass. The value of consumed O2 was transformed in kcal multiplying it by 5 (constant kcal per liter of O2). A mean energetic expenditure of 740.42 kcal and 494.64 kcal were observed as results for the referees and assistants, respectively. In conclusion, their physical activity is of moderate intensity, as the performance of the referee and the assistant represented an oxygen consumption equal or less than 16.17 ml/kg/min in 73.98% and 89.97% of the total game time, respectively.